2019
DOI: 10.3390/nano9081132
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives on the Electronic and Geometric Structure of Au70S20(PPh3)12 Cluster: Superatomic-Network Core Protected by Novel Au12(µ3-S)10 Staple Motifs

Abstract: In order to increase the understanding of the recently synthesized Au70S20(PPh3)12 cluster, we used the divide and protect concept and superatom network model (SAN) to study the electronic and geometric of the cluster. According to the experimental coordinates of the cluster, the study of Au70S20(PPh3)12 cluster was carried out using density functional theory calculations. Based on the superatom complex (SAC) model, the number of the valence electrons of the cluster is 30. It is not the number of valence elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Density functional theory (DFT) methods are most oen employed in theoretical investigations, as they are capable to accurately describe electronic, geometrical, and vibrational structure of gold clusters and nanoparticles. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] In particular, the DFT-based simulation of IR, Raman, and UV-vis spectra has been achieved for a range of gold clusters, thus providing useful theoretical ngerprints to distinguish between bonding arrangements and orientations between gold atoms and ligands, and ligandligand interactions within clusters. 23,[30][31][32][33][34] Unfortunately, DFT calculations can become prohibitively expensive with system size, 35 and routine theoretical investigations are limited to moderate system sizes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Density functional theory (DFT) methods are most oen employed in theoretical investigations, as they are capable to accurately describe electronic, geometrical, and vibrational structure of gold clusters and nanoparticles. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] In particular, the DFT-based simulation of IR, Raman, and UV-vis spectra has been achieved for a range of gold clusters, thus providing useful theoretical ngerprints to distinguish between bonding arrangements and orientations between gold atoms and ligands, and ligandligand interactions within clusters. 23,[30][31][32][33][34] Unfortunately, DFT calculations can become prohibitively expensive with system size, 35 and routine theoretical investigations are limited to moderate system sizes.…”
Section: Introductionmentioning
confidence: 99%
“…triphenylphosphine (PPh 3 ) is replaced by phosphine (PH 3 ) or trimethylphosphine (PMe 3 ). 17,18,22,25,26,28,29,36 This, as with the complete ligand removal approach, has the additional benet that conformational searching is simplied, as the torsions of the three phenyl groups per ligand give rise to a large number of local minima with similar energies. Nevertheless, it is well known that the electronic effects of the larger ligands are different from those of the smaller ones, for instance inductive effects, [36][37][38][39] and a computational truncation of the ligands will inuence the chemistry and therefore description of the catalytic properties in calculations.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this Special Issue on "Supramolecular Gold Chemistry" was to provide a unique international forum aimed at covering a broad description of results involving the supramolecular chemistry of gold with a special focus on the gold-sulfur interface leading to hybrid materials, ranging from gold-thiolate complexes, [3] to thiolate-protected gold nanoclusters [4][5][6][7][8][9][10][11] and gold-thiolate supramolecular assemblies or nanoparticles. [12][13][14] The role of thiolates on the structure and optical features of gold nanohybrid systems (ranging from plasmonic gold nanoparticles and fluorescent gold nanoclusters to self-assembled Au-containing thiolated coordination polymers) has been highlighted in the review article by Csapó and coworkers [14].…”
mentioning
confidence: 99%
“…Cheng and coworkers theoretically investigate Au 70 S 20 (PPh 3 ) 12 using density functional theory calculations. The electronic and geometric structure of Au 70 S 20 (PPh 3 ) 12 is further addressed based on the popular divide and protect concept and the superatom network model [7].…”
mentioning
confidence: 99%
“…Cheng and coworkers also performed quantum chemical calculations on Au70 and showed that Au70 might be described via a superatom 133 network model exhibiting 2e-Au 4 superatoms. 134 In much broader studies Zhou et al and Cheng et al showed the important impacts of the Au 4 motif onto the structures of metalloid Au clusters. 135,136 …”
mentioning
confidence: 99%